Languages in the Avenida Lourenço Peixinho in Aveiro: educational potential to raise awareness of linguistic and cultural diversity - Santos, Sara (2019)
Acknowledging the educational potential of linguistic landscapes, this paper sets out to: - identify the foreign languages present in the Avenida Lourenço Peixinho in Aveiro (Portugal) and the linguistic landscape signs in which they appear; - propose an interdisciplinary set of activities for the exploration of the linguistic landscape in the Avenida. To address these aims, an exploratory case study was conducted. Photographic data was collected in the Avenida and it was subject to content analysis. The analysis of the linguistic landscape displayed shows that English is the foreign language with the greatest presence and that the diversity of languages is low with a scarce presence of immigration languages such as Chinese. This exploratory experience was the basis for the creation of an interdisciplinary set of pedagogical activities (involving English, Spanish, History and Geography subjects) aimed at secondary education, providing some suggestions to explore linguistic landscapes as educational resources for the purposes of increasing students and educational community’s awareness concerning linguistic and cultural diversity.